Perpetrators of Spreading Hoaxes Through Social Media During the 2019 Presidential Election in Indonesia - Albasier, Muhammad Heykal; Alhadi, Muhammad Nurcholis; Muslim, Ikhwanul (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The spread of hoaxes on social media during elections in Indonesia has become a troubling phenomenon and threatens the integrity of democracy.Purposes of the Research: This study aims to examine the legal arrangements in the Electronic Information and Transactions Law and criminal liability for perpetrators of spreading hoaxes on social media during elections.Methods of the Research: The research method used is normative juridical research with a legislative approach and qualitative analysis of secondary data in the form of legal documents, literature, and previous research results.Findings of the Research: The results show that the Electronic Information and Transactions Law provides a strong legal basis to take action against the perpetrators of hoax distribution with quite severe criminal threats. However, the implementation of this law still faces challenges, especially in terms of law enforcement and public education on digital literacy. This study suggests the need for increased cooperation between the government, social media platforms, and the public in combating hoaxes and improving digital literacy to prevent the spread of misleading information.